IMPROVING STUDENTS’ CRITICAL THINKING IN READING COMPREHENSION THROUGH DIRECTED READING THINKING ACTIVITY AT SMAN 2 ENREKANG - Fadillah, Nur Afni; Nur Devi Bte Abdul; Ratu Yulianti Natsir, (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2022)
This research aimed to know the improvement students’ critical thinking in reading comprehension through Directed Reading Thinking Activity (DRTA) at the first grade in SMAN 2 ENREKANG. The method of this research was pre-experimental research. The sample of this research consisted of experiment class. Namely, class X IPA 4 were 30 students. In the class used Directed Reading Thinking Activity (DRTA). The sample were taken by cluster sampling technique.Based oon the findings, it was found there were relevance and accuracy aspects of critical thinking that signifiicantly increased. The significance value (2-tailed) was 0.000 ( P>0.05 ). And the T-test value is higher that T-table value, the table showed result of 4.722>2.045 it means that there was improvement in the students’ critical thinking in reading comprehension before and after gave treatment used narrative text. Therefore that the result of the pre-test and post-test was significance different. Based on the descriptive statistic, the pre-test and post-test prove the post-test is higher. Based on the explanation, Directed Reading Thinking Activity (DRTA) can improve the students’ critical thinking in reading comprehension.